Sociedade em rede e internet : direitos fundamentais em diálogo - Aguiar, Rodrigo Goulart (2015)
The network society has had its boundaries outlined through the information and communication technologies - ICTs, especially after the birth of the Internet. In that context, based on the rules of human dignity and free personality development, the acknowledgment of fundamental rights to access the Internet is a clear fact. In the virtual environment, the scales of space and time have changed dramatically. The quantitative growth of information broadcasted in the Web has gained qualitative features, representing risks to rights of several natures, such as the right to privacy and the protection of personal data. Government entities and especially private companies worldwide have been using advanced technologies of massive data processing. The result of such process is the elaboration of individual and collective profiles which are used as a basis for the implementation of software for marketing and discrimination usage. In that sense, once we acknowledge the symbiotic relation between Law and Internet, the necessity of legal regulation of the Internet amongst the surveillance society becomes clear. Aware that the traditional legal approach does not follow the technology evolution of the virtual environment, new regulation models are necessary. Under this view, there is the mixed model suggested by Lawrence Lessig, from the mutual interaction of the social standards, market, Law and the architecture of the Web. As a complement to the author’s suggestion, there is the necessary reflection about the Internet users’ behavior in the Web, the implementation of international cooperation policies, as well as a reinterpretation of the contracts in the virtual environment. Such situation reveals the sovereign regulator nature of the Law and boosts its effectiveness in the cyberspace.